Incorporação de tecnologias na comunidade quilombola Grotão em Filadélfia – TO - Holanda, Mayza Jardim (2020)
The presence of technologies in traditional communities is currently occurring as a result of technical and scientific advances that have been expanded and consolidated by the globalization process. This dissertation presents the influence of the insertion of technologies from external sources to the community, in the traditional way of life of the quilombola community Groton in Philadelphia - TO. he research aimed to understand the uses and interferences of different technologies in the livelihoods of the Quilombola Grotão community. The methodological construction was based on Oral History, since it intends to go beyond the investigation of quilombola cultural practices and the resignifications caused by the use of technologies, and also has the intention of analyzing and problematizing the meaning of speeches of the remaining quilombolas. Interviews were used, based on the life history, application of open and semi-structured questionnaires, evidencing deponents according to some criteria, such as the age group and its social role within the community. In this sense, emphasis was placed on the patriarchs, the leaderships and the quilombolas who stood out through their trajectory in the community. This research also used documentary sources, originated from books, theses, dissertations, articles, websites. The theoretical framework allowed us to base and support the construction of all research, as field knowledge is a great contribution to the understanding of the current dynamics in the community and knowledge of the existing technological devices. The dissertation addresses, in the general context, the historical slavery issue in Brazil and a brief explanation about the quilombolas in the states of Tocantins and Maranhão. It presents a discussion about traditional communities and the appropriation of techniques and technology, addressing the changes and permanences mediated by them. It also refers to cultural practices, technical-technological uses, contemporary appropriations and re-significances, highlighting the succinct process of modifications that occurred in the community, especially after the implementation of electric energy, to the present day with the use of television and the mobile telephony. It is concluded that there are multiple techniques and technologies, connected to the dynamics of everyday life in the Grotto community. The community handles much more technique and technology than can be expected from a community as a remnant of quilombo in the quest for its maintenance and survival in the current days.